Inert Coats of Magnetic Nanoparticles Prevent Formation of Occlusive Intravascular Co-aggregates With Neutrophil Extracellular Traps - Bilyy, Rostyslav; Unterweger, Harald; Weigel, Bianca; Dumych, Tetiana; Paryzhak, Solomiya; Vovk, Volodymyr; Liao, Ziyu; Alexiou, Christoph; Herrmann, Martin; Janko, Christina (Frontiers in Immunology, 2018)
If foreign particles enter the human body, the immune system offers several mechanisms of response. Neutrophils forming the first line of the immune defense either remove pathogens by phagocytosis, inactivate them by degranulation or release of reactive oxygen species or immobilize them by the release of chromatin decorated with the granular proteins from cytoplasm as neutrophil extracellular traps (NETs). Besides viable microbes like fungi, bacteria or viruses, also several sterile inorganic particles including nanoparticles reportedly activate NET formation. The physicochemical nanoparticle characteristics fostering NET formation are still elusive. Here we show that agglomerations of non-stabilized iron oxide nanoparticles induce NET formation by isolated human neutrophils, in whole blood experiments under static and dynamic conditions as well as in vivo. Stabilization of nanoparticles with biocompatible layers of either human serum albumin or dextran reduced agglomeration and NET formation by neutrophils. Importantly, this passivation of the SPIONs prevented vascular occlusions in vivo even when magnetically accumulated. We conclude that higher order structures formed during nanoparticle agglomeration primarily trigger NET formation and the formation of SPION-aggNET-co-aggregates, whereas colloid-disperse nanoparticles behaved inert and are alternatively cleared by phagocytosis.